Short-term contamination changes of 137Cs and 90Sr in ecosystems elements of high-ageoakforests in the Chernobyl Nuclear Power Plant exclusion zone - Garbaruk, Dmitriy; Voronetskaya, Alesya; Shumak, Svetlana; Turchin, Larisa; Uglyanets, Anatoliy (Journal of the Belarusian State University. Ecology, 2025)
Studies in wood sorrel, goutweed and riverbed–floodplain oak forests in the exclusion zone of the Chernobyl nuclear power plant, it was established that at the current stage of the consequences of the nuclear disaster against the general background of mitigation of the radiation situation, there are significant differences in the directions and rates of short-term changes (from 2018 to 2024) in the indicators of contamination of soils and structural components of 137Cs and 90Sr of the main tiers of plantations. The gamma dose rate and soil contamination with both radionuclides decreased in all types of oak forests, except for the soil of the riverbed–floodplain oak forest, where the 90Sr content increased. Current changes in the parameters of 137Cs and 90Sr contamination of oak tree organs and tissues, undergrowth and understorey plants, parts of phytomass of background species of living ground cover were of different vectors and magnitudes and depended on the plant species, forest type and year of observation. The ranked series of 137Cs and 90Sr transition coefficients into components of oak trees and organs of undergrowth and understorey differed by forest types and years of observation. For oak trees, the transfer of 137Cs and 90Sr to wood was minimal, while the transfer of 137Cs to acorns and leaves was maximal. In 2024, the ranked series of 137Cs transition coefficients was common for all forest types – “wood < bark < roots < branches < acorns < leaves”. The most frequent distribution of undergrowth and understorey organs according to the values of 137Cs transition coefficients in them was the series “trunks < roots < leaves”, 90Sr – “trunks < leaves < roots”. An increase in the specific activity of 90Sr in the aboveground and underground phytomass of May lily was revealed in the series of forest types “riverbed–floodplain oak forest < wood sorrel oak forest < goutweed oak forest”.
Keywords: Чернобыльская атомная электростанция; зона отчуждения; дубрава; почва; элемент фитоценоза; 137Cs и90Sr; удельная активность; коэффициент перехода